Point-of-Care Ultrasound Identification of an Abdominal Hernia. Issue 8 (August 2017) - Alfonzo, Michael; von Reinhart, Anna; Riera, Antonio
Abstract : Abstract: Pediatric emergency medicine physicians may be able to use point-of-care ultrasound (POCUS) as a tool to evaluate abdominal wall masses. We present a case of a 2-month-old infant with a lower abdominal mass identified as a hernia sac by POCUS. It was initially thought to represent a Spigelian-type abdominal wall hernia but subsequently determined to be an unusual presentation of an inguinal hernia with testicular entrapment. We review each of these diagnoses in addition to relevant POCUS findings. Abstract : Supplemental digital content is available in the text.